The initiation of a multidisciplinary bladder cancer clinic and the uptake of neoadjuvant chemotherapy: A time-series analysis - Nayan, Madhur; Bhindi, Bimal; Yu, Julie L.; Mamdani, Muhammad; Fleshner, Neil E.; Hermanns, Thomas; Chung, Peter; Milosevic, Michael; Bristow, Robert; Warde, Padraig; Hamilton, Robert J.; Finelli, Antonio; et al. (Canadian Urological Association Journal, 2016)
Introdcution: While level 1 evidence supports the use of neo-adjuvant chemotherapy (NAC) for patients with muscle-invasive bladder cancer (MIBC), its uptake has been underwhelming even in academic centres. Our aim was to determine if the initiation of a multidisciplinary bladder cancer clinic (MDBCC) in 2008 at our institution, where patients are assessed simultaneously by bladder cancer-focused urologists and radiation oncologists with easy access to a medical oncologist, was associated with an increased use of NAC. Methods: Patients with MIBC initiating treatment between July 2000 and June 2013 were identified and classified by academic year (July 1 to June 30). Time-series analyses using interventional autoregressive integrated moving average (ARIMA) models with ramp intervention functions were then conducted. A sensitivity analysis was performed on clinical N0 patients. Results: The cohort included 278 patients: 168 from 2000-2007 and 110 from 2008-2012 (academic years). Forty-two (15.1%) patients received NAC and 74 (26.6%) received adjuvant chemotherapy (AC). Overall the proportion of patients receiving NAC increased from 7.7% before the MDBCC to 47.6% in 2012 (Interventional ARIMA p=0.036). The results were similar when restricting to cN0 patients (p<0.001). NAC use gradually increased over time regardless of MDBCC attendance, although the proportion of patients receiving NAC appears to have risen more sharply among MDBCC attendees. Conclusions: At our institution, the initiation of the MDBCC was temporally associated with increased use of NAC. In addition to multidisciplinary collaboration, having a critical mass of NAC physician advocates and support from institutional leaders are essential to the uptake of NAC.